Effects of Ti Addition on the Characteristics of Al-10Zn-6Mg-2Si/ZrO2 Composites Produced by Squeeze Casting - Prameshvara, Qesha Diva; Lestari, Pipin Indah; Sofyan, Bondan Tiara (Journal of Materials Exploration and Findings, 2024)
Metal matrix composite (MMC) with 7xxx aluminum matrix is potential for ballistic applications due to the combination of strength, toughness, and light weight. Previous study successfully produced aluminum-based composites with SiC particles which were able to stop type III bullet, however cracks remained on back of the plate. Therefore, in this research, SiC was replaced by zirconia (ZrO2) due to its high fracture toughness. Ti-B grain refiner was added to further improve toughness through grain boundary strengthening mechanism. This research developed 5 vol.% ZrO2 strengthened Al-10Zn-6Mg-2Si composite with addition of Al-5Ti-1B grain refiner produced through squeeze casting process. The Ti content was varied 0, 0.058, 0.073 and 0.0104 wt.%. The composite was solution treated at 450°C for 1 hour, then aged at 200°C for 1 hour. Material characterization Rockwell B hardness testing, impact testing, microstructural observation by using optical microscopy included Scanning Electron Microscope (SEM) with Energy Dispersive X-ray (EDX) and X- ray Mapping. The results showed that addition of Ti resulted in an increase in as-cast hardness as well as aged hardness. This was followed by the decrease in porosities, impact values and Dendrite Arm Spacing (DAS). However, there was an anomaly in the composite containing 0.078 wt. % Ti, due to the fact that this composite was produced by remelting. Actual hardness was lower than theoretical hardness calculated by rule of mixture because ZrO2 particles were not well mixed in the matrix. This was confirmed by the observation of microstructure, SEM and OES, that were not able to detect either ZrO2 or Zr element. The microstructures consisted of Mg2Si in irregular, oval and Chinese script morphologies, aAl8Fe2Si, which was also in Chinese script morphology and bAl5FeSi in needle shape.